Field sampling methods for investigating forest-floor bryophytes: Microcoenose vs. random sampling - Ilić, Miloš; Igić, Ružica; Ćuk, Mirjana; Vukov, Dragana (Archives of Biological Sciences, 2018)
Paper description: Despite the importance of bryophytes in forests, these plants are usually ignored in forest ecosystem studies, and a standardized methodology for quantifying bryophyte abundance in forest communities is still lacking. Among several used methods, quadrat sampling is the most common. The microcoenose method for quantifying bryophytes is a systematic sampling method developed in broadleaved forests in China, but it has never been tested and compared with the random sampling method in temperate beech forests. The high applicability of the microcoenose method in a broadleaved forest with patchy bryophyte distribution is a step towards its standardization for bryophyte quantification. Abstract: Because of the high importance of bryophytes in forest ecosystems, it is necessary to develop standardized field sampling methodologies. The quadrat method is commonly used for bryophyte diversity and distribution pattern surveys. Quadrat size and the position of quadrats within the studied area have a significant influence on different analyses. The aim of the present study was to define the minimum quadrat size appropriate for sampling ground bryophytes in temperate beech forests, to compare two different field sampling methods for research on ground bryophytes, the random and microcoenose methods; and to test the adequacy of the microcoenose sampling method in temperate beech forests. Research was carried out on Fruška Gora mountain (Serbia) at four different sites. All sites contained temperate broadleaf forest vegetation, predominantly Fagus sylvatica, but also included various other tree species. Systematic sampling based on nested quadrats was used to determine the minimum sampling area. Random sampling was performed using 10 or 20 microplots (minimum area quadrat), randomly located within 10x10 m plots. Microcoenose sampling is a systematic sampling method based on the fact that every bryophyte fragment on the forest floor is a separate microcoenose. These methods were compared using the following criteria: species richness; Shannon’s diversity index and evenness measure; coverage of dominant species, and the time needed for sampling. The microcoenose sampling method has proven to be highly applicable in temperate beech forests in terms of species richness and diversity, in contrast to random sampling, which was not suitable for bryophyte flora with a patchy distribution. https://doi.org/10.2298/ABS180422020I Received: April 22, 2018; Revised: May 9, 2018; Accepted: May 10, 2018; Published online: May 15, 2018 How to cite this article: Ilić M, Igić R, Ćuk M, Vukov D. Field sampling methods for investigating forest-floor bryophytes: Microcoenose vs. random sampling. Arch Biol Sci. 2018;70(3):…